Physicochemical and spectroscopic characterissation of Malaysian honeys for potential medicinal applications - Abd Aziz, Zul Hadif; Helal Uddin, A.B.M.; Mohd Aminudin, Norfatini; Begum, Taslima; Ahmed, Qamar Uddin; Liew, Kai Bin (Malaysian Institute of Chemistry, 2025)
Honey, a natural product from honeybees, is well-known for its therapeutic properties in managing various illnesses and health conditions. It contains a rich array of bioactive compounds, including polyphenols, flavonoids, amino acids, sugars, and essential minerals. In this light, rigorous quality control is essential to ensure the preservation and validation of these health-promoting attributes. In this study, multiple analytical techniques were employed to examine the quality of honey samples, including refractometry, electrical conductivity, UV-Vis spectroscopy, and FTIR-ATR analysis. As shown in the findings, the physicochemical parameters of all tested samples - pH (3.44 - 4.42), refractive index (1.47028-1.49037) water content (18.45% - 26.55%), viscosity (14439cP - 29661cP), and electrical conductance (97.71μS/cm - 769.56μS/cm), are within accepted quality standards and comparable to those of Manuka honey, indicating their potential for therapeutic applications. Additionally, UV-Vis and FTIR analyses revealed distinctive absorbance patterns that facilitated the differentiation of honey types and their geographical origins. Overall, this study underscores the importance of integrating physicochemical profiling with spectroscopic methods to assess honey quality for medicinal use comprehensively.